3-Hydroxyphenylacetic Acid Induces the Burkholderia cenocepacia Phenylacetic Acid Degradation Pathway – Toward Understanding the Contribution of Aromatic Catabolism to Pathogenesis - Imolorhe, Ijeme A.; Cardona, Silvia T. (Frontiers in Cellular and Infection Microbiology, 2011)
The phenylacetic acid (PA) degradative pathway is the central pathway by which complex aromatic compounds (e.g. styrene) get degraded. Upper pathways for different aromatic compounds converge at common intermediate phenylacetyl-CoA, which is then metabolized to succinyl-CoA and acetyl-CoA. We previously made a link in Burkholderia cenocepacia between phenylacetic acid (PA) degradation and virulence by showing that insertional mutagenesis of paaA and paaE results in PA-conditional growth and an attenuated killing phenotype in the Caenorhabditis elegans model of infection. Insertional mutagenesis of paaK1, which encodes a phenylacetyl-CoA ligase, did not result in a PA-conditional growth probably due to the presence of a second similar gene (paaK2) encoding another phenylacetyl-CoA ligase (PaaK2). Recently published crystallographic and enzyme kinetics studies comparing the two ligases show that PaaK1 is better able to bind hydroxylated PA derived molecules such as 3-hydroxyphenylacetic (3-OHPA) acid and 4-hydroxyphenylacetic acid (4-OHPA) due to its having a larger binding pocket than PaaK2. However, the biological significance of this finding remains unanswered. In this study, we demonstrate that 3-OHPA but not 4-OHPA, induces the phenylacetic acid degradative pathway in Burkholderia cenocepacia K56-2. Using reporter activity assays, we show paaK1-dependent induction of the PA degradative pathway when 3-OHPA is added to the culture medium. To shed light on a possible relevance of this finding to pathogenicity, we compared the pathogenicity of the paaK1 deletion mutant with that of the wild type in C. elegans. Results show that the loss of PaaK1 function does not equal to a loss of pathogenicity. Taken together our results suggest that 3-OHPA but not 4-OHPA may be degraded through the PA degradative pathway but that 3-OHPA-related intermediates may not be relevant to pathogenesis as previously thought.